Dynamic Analysis of a DC-DC Multiplier Converter - Mayo-Maldonado, J. C.; Salas-Cabrera, R.; Rosas-Caro, J. C.; Cisneros-Villegas, H.; Gomez-Garcia, M.; N.Salas-Cabrera, E.; Castillo-Gutierrez, R.; Ruiz-Martinez, O. (IntechOpen, 2011)
None